(untitled) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2021)
International trade plays an important role in the economic development of a country. One economic approach that focuses on commodity prices is called Raul Prebisch and Hans Singer or often the Prebisch-Singer hypothesis. The COVID-19 pandemic has had an impact on the weakness of the world economy. The purpose of this study is to analyze the long-term and causality between exports of primary commodities in prices and to describe the pandemic conditions in accordance with this hypothesis. This study uses two methods, namely Cointegration and Granger Causality. The variables used are the value of the export volume of several primary commodities on inflation and exchange rates. In the monthly period from 2019-2021. The results show a unidirectional relationship between the value of primary commodity exports with inflation and also on the exchange rate. Long-term relationship is not in accordance with the Prebisch Singer Hypothesis. The COVID-19 pandemic has resulted in the disruption of the level of economic activity (lockdown). As a result, the primary price level has decreased and will return to stability in the future.